Parent–child perceptions of quality of life: Implications for health intervention - Gaspar, Tania (2013)
The KIDSCREEN-52 is an instrument that assesses 10 dimensions of health-related quality of life (HRQoL). It was developed as a result of studies by the European KIDSCREEN Group, University of Berlin (www.kidscreen.org; see also Bisegger et al., 2005). During the Portuguese validation process, a model was developed to examine the perceptions of children and their parents on these dimensions. Structural equation modelling was used in order to estimate the fit of this model, in both cases according to gender and age. The specific aim of the present study was to examine the extent to which results differ by gender and age. An additional aim was to explore differences between the child and parent versions of the instrument, globally as well as by gender and age of the children. The results are based on a nationally representative sample of 3195 children from 5th and 7th grades. Data from each child were paired with data from their parents (2256 matched sets of data were generated). Most of the subscales exhibited good internal consistency in both the children’s and parent’s versions of KIDSCREEN-52, with values of the alpha coefficient approaching or above .80 for most scales. The exception was the subscale concerned with self-perception where the coefficient was approximately .64 for both children and parents. Subscale scores for children’s and parents’ versions correlated moderately strongly in the sample of matched pairs. This indicates that children and their parents view their health-related quality of life consistently,although parents tend to perceive their children’s quality of life as better than their children do. Analysis of variance suggested that there were small differences in scores associated with gender and age. The results confirm that the KIDSCREEN-52 questionnaire is a relevant instrument to estimate the perception of quality of life both in children and their parents. The findings that parents are not totally aware of their children’s subjective health-related quality of life perceptions and that parents have different perceptions according to the gender and the age of their children, have implications for professional practice and intervention with families of school-aged children.